2020
DOI: 10.1021/acs.analchem.0c02845
|View full text |Cite
|
Sign up to set email alerts
|

Releasing Nonperipheral Subunits from Protein Complexes in the Gas Phase

Abstract: The quaternary structure is an important feature regulating protein function. Native mass spectrometry contributes to untangling quaternary structures by preserving the integrity of protein complexes in the gas phase. Tandem mass spectrometry by collision-induced dissociation (CID) can then be used to release subunits from these intact complexes, thereby providing structural information on the stoichiometry and topology. Cumulatively, such studies have revealed the preferred release of peripheral subunits duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…With LPGS established as the best ligand among the polysulfates tested here,analysis on compound-RBD binding was further conducted using native mass spectrometry, ac ommon technique to study non-covalent complexes of proteins. [39,40] Figure 4c shows the results of the mass spectrometry experiments with different amounts of heparin or LPGS added to the RBD solution.…”
Section: Methodsmentioning
confidence: 99%
“…With LPGS established as the best ligand among the polysulfates tested here,analysis on compound-RBD binding was further conducted using native mass spectrometry, ac ommon technique to study non-covalent complexes of proteins. [39,40] Figure 4c shows the results of the mass spectrometry experiments with different amounts of heparin or LPGS added to the RBD solution.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, additional fragmentation of the ejected monomeric subunits can be used to reveal the identity of the subunits. However, from all of the available tandem MS studies on protein assemblies, it also has become apparent that the smaller peripheral subunits often display a preference to be ejected and also that the structures of the activated protein complexes can drastically change when transferred into the gas phase and even more so upon activation . To summarize, although it should be used with care, tandem MS studies can provide essential structural information that is not easily accessible by other means, as briefly illustrated below with a few prominent examples.…”
Section: Tandem Mass Spectrometry and Ion Activation In Native Msmentioning
confidence: 99%
“…Collisional activation in the gas phase has been used most extensively in native MS for protein complex dissociation, and it is featured by a wide range of instruments. Recently, Wang et al demonstrated that although collisional dissociation (CID/CAD/HCD) preferentially results in ejection of peripheral subunits, less exposed nonperipheral subunits also can be ejected from certain protein assemblies. Studying the 20S core proteasome of Thermoplasma acidophilum, engineered antibody complexes, and elongated complement protein complexes, they identified two major pathways by which nonperipheral subunits can be released.…”
Section: Tandem Mass Spectrometry and Ion Activation In Native Msmentioning
confidence: 99%
“…CID is well-known to eject highly charged monomers from a noncovalent protein complex, leaving an (N-1)­mer intact. ,,,,,, Multiple monomeric subunits can be stripped from a complex through typical collisional activation with target gas (involving multiple low-efficiency collisions), although whether the cleavages occur simultaneously or (more likely) sequentially is unclear. , Sequential removal of monomers was suggested by Benesch et al, who observed production of 11mer of TaHSP16.9 12mer at modest CID collision energies with a concurrent disappearance of the 12mer, but at high collision energies the 11mer species decreased in relative abundance concurrent with appearance of a 10mer. It has also been reported that peripheral subunits are preferentially released. ,,, Wang et al found that nonperipheral subunits could be released through secondary dissociation after primary removal of peripheral subunits or directly from charge-reduced or elongated protein complexes . Song studied dissociation of the heterohexamer TNH (untagged) by CID and SID and observed changes in preferential ejection of monomers via CID as a result of altered charge density on the complex .…”
Section: Mechanism Of Sid For Protein Assembliesmentioning
confidence: 99%